Infant formula with added Lacticaseibacillus rhamnosus GG supported adequate growth and was well tolerated in healthy term infants: a randomized controlled trial - Berseth, Carol Lynn; Yeiser, Michael; Harris, Cheryl L.; Kinnaman, Jennifer N.; Lappin, Victoria; Wampler, Jennifer L.; Zhuang, Weihong; Vanderhoof, Jon (Frontiers in Pediatrics, 2024)
Lacticaseibacillus rhamnosus GG (LGG) is a well-studied prebiotic with a history of safe use. In this double-blind, prospective study, growth and tolerance were evaluated in healthy term infants randomized to: marketed, routine intact cow's milk protein-based formula (Control, n=172) or a similar investigational formula with added LGG (INV-LGG, n=179; 10 6 CFU LGG®/g powder) from 14 to 120 days of age. Anthropometrics, stool characteristics, fussiness, and gassiness were evaluated through Day 120. Medically confirmed adverse events were recorded throughout the study period. The primary outcome was rate of weight gain from Day 14-120. Of 351 infants enrolled, 275 completed (Control, n=131; INV-LGG, n=144). No significant group differences in rate of weight gain from Day 14-120 were detected. Study formula acceptance and tolerance was good with no significant differences in study discontinuation due to study formula or parentreported gassiness, stool frequency, or stool consistency; however mean fussiness relative to normal was significantly lower for INV-LGG vs Control at Days 60 and 90. In healthy term infants, a routine intact cow's milk protein-based formula with added LGG supported adequate growth and was well tolerated. Further studies are needed to evaluate potential benefits for fussiness and efficacy outcomes.